Preliminary Neutronic Studies on RSG-GAS Fuel Element with 4.8 grU/cc and Burnable Poison Wire for Reactivity Reduction - Luthfi, W.; Setiadipura, T.; Su’ud, Z. (National Research and Innovation Agency, 2025)
High-density fuel can increase the operating cycle of a nuclear reactor. The G.A. Siwabessy Multipurpose Reactor (RSG-GAS) is a research reactor owned by Indonesia that currently uses 19.75 % enriched uranium silicide fuel (U3Si2-Al) with a uranium density of 2.965 grU/cc. Previous studies have shown that high-density fuel, 4.8 grU/cc, can be used in the RSG-GAS core to extend the operating cycle. Previous studies related to high-density fuel conversion scenarios included a temporary conversion process to a density of 3.55 grU/cc before being increased to 4.8 grU/cc. However, the previous conversion process requires the addition of control rods to suppress the excess reactivity of the RSG-GAS. The current study focuses on determining the configuration of burnable poison wire for the standard fuel element of RSG-GAS (FE) made of cadmium and hafnium to suppress the reactivity (k-inf) of the 4.8 grU/cc fuel element so it could have an initial reactivity closer to the 2.965 grU/cc fuel. 5 pairs of 0.4 mm diameter Cd-wire coated with 0.1 mm AlMg2 cladding can suppress the reactivity of the fuel assembly, while 7 pairs of 0.8 mm diameter Hf-wire without cladding could suppress reactivity longer. The temperature coefficient of reactivity for the moderator temperature (MTC) and fuel temperature (FTC) also becomes more negative in high-density FE RSG-GAS while the amount of Pu-239 produced increases in high-density fuel element.